Obesity-associated Neurochemical Regulators of Homeostatic and Hedonic Food Intake - Hasmik S. Harutyunyan; Gayane S. Vardanyan; Alla L. Shaljyan; Anahit V. Saharyan; Mikhail I. Aghajanov (Research Highlights in Disease and Health Research Vol. 9, 2023)
The problem of obesity shows a growing pattern. 25% of the population of the planet is overweight with a body mass index (BMI) of 25-30 and about 8% is obese with BMI over 30. Despite the high rate of morbidity, the pathogenesis of obesity underlying uncontrolled eating behavior still has many uncovered aspects. Genetic and environmental factors, several regions of the CNS, various neurotransmitters, and neuropeptides, are involved in the central mechanisms that control eating behavior. Physiologically food is consumed for homeostatic and hedonic purposes, regulated by two distinct but closely interconnected systems: the hypothalamic and brain reward systems. Hedonic eating usually exceeds the caloric threshold for the physiological requirement of the organism for energy and structural material. In this context, dopamine and serotonin are considered the most important neurotransmitters. Hence, the endocannabinoid and opiate systems also have been shown to have particular weight in the regulation of food intake and sense of pleasure. In this chapter, we highlight the main neurochemical regulators involved in the peripheral and central mechanisms of hedonic eating causing overweight and obesity.